The RGEC Method in Analyzing Bank Health: A Case Study of Bank Nagari - Dodi Suryadi; Putri Intan Permata Sari (SAFE-Network, 2026)
This study aims to analyze the health level of a bank using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital) at Bank Nagari during the 2020–2024 period. The RGEC method is a risk-based bank rating approach that evaluates bank performance through four main aspects: risk profile, corporate governance, profitability, and capital adequacy. This research employs a descriptive quantitative approach using secondary data obtained from the annual financial reports of Bank Nagari and official publications from the Financial Services Authority. The analysis is conducted by calculating financial ratios representing each RGEC component, including Non-Performing Loan and Loan to Deposit Ratio for Risk Profile, self-assessment for Good Corporate Governance, Return on Assets, Return on Equity, Net Interest Margin, and Operating Expenses to Operating Income for Earnings, as well as Capital Adequacy Ratio for Capital. The results indicate that overall, Bank Nagari’s health level is categorized as healthy to very healthy throughout the observation period. The Risk Profile shows significant improvement in NPL, which falls into the very healthy category, although LDR remains in the fairly healthy category. The GCG aspect demonstrates consistent performance in the healthy category. In terms of Earnings, most indicators are classified as very healthy, despite ROE requiring further improvement. Meanwhile, the Capital aspect shows a very strong condition, with CAR consistently in the very healthy category. In conclusion, Bank Nagari exhibits stable and strong performance; however, improvements are still needed in liquidity management, corporate governance, and capital utilization efficiency to achieve an optimal overall health level.